2007
DOI: 10.1093/ndt/gfm237
|View full text |Cite
|
Sign up to set email alerts
|

No clear evidence of ACEi efficacy on the progression of chronic kidney disease in children with hypodysplastic nephropathy report from the ItalKid Project database

Abstract: We conclude that ACEi treatment does not significantly modify the naturally progressive course of hypodysplastic nephropathy in children and further studies are necessary before such treatment is routinely proposed for anti-progression purposes in children with CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 19 publications
(23 reference statements)
1
35
0
2
Order By: Relevance
“…In addition, use of ACE inhibitors or ARBs was associated with lower baseline urine protein excretion in children with CKD owing to glomerular, but not hypodysplasia causes in the CKiD study [44]. The lack of effect of renin-angiotensin system blockers on CKD progression in children with hypodysplasia was also seen in a case-control study by the ItalKid Project [45]. In the ESCA PE trial, intensified blood pressure control did slow disease progression in children with hypodysplasia, but the study was not designed to attribute the outcomes to ACE inhibitor use specifically [4].…”
Section: First-line Antihypertensive Medicationmentioning
confidence: 77%
“…In addition, use of ACE inhibitors or ARBs was associated with lower baseline urine protein excretion in children with CKD owing to glomerular, but not hypodysplasia causes in the CKiD study [44]. The lack of effect of renin-angiotensin system blockers on CKD progression in children with hypodysplasia was also seen in a case-control study by the ItalKid Project [45]. In the ESCA PE trial, intensified blood pressure control did slow disease progression in children with hypodysplasia, but the study was not designed to attribute the outcomes to ACE inhibitor use specifically [4].…”
Section: First-line Antihypertensive Medicationmentioning
confidence: 77%
“…Although there were no statistically significant differences in Up/c's among subjects with nonglo- merular causes of CKD whether or not ACEI/ARB medications were used, there is insufficient data to conclude that there is no benefit of using such agents among patients with nonglomerular disease. Recently, Ardissino et al reported that there was no clear evidence of ACEI efficacy on the progression of CKD in children with hypodysplastic nephropathy (30). In their cohort study comparing 41 patients on ACEI therapy and control patients who were not on ACEI therapy, both groups had stable kidney function, with the average decline of Ϫ0.31 ml/min/ 1.73m 2 /yr with ACEI therapy and Ϫ0.33 ml/min/1.73m 2 without ACEI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Children with Up/c levels Ͻ0.9 showed a slower decline of renal function and a higher rate of renal survival than those with baseline Up/c level Ͼ0.9 at 5 years (16). Furthermore, ACEi did not significantly delay the progressive decline in renal function in children with lower proteinuria compared with matched controls (17). In the ESCAPE (Effect of Strict Blood Pressure Control and ACE Inhibition on the Progression of CRF in Pediatric Patients) trial, ACEi reduced protein excretion by approximately 50% in all forms of nephropathy within the first 6 months in children with CKD (18,19).…”
Section: Novel and Traditional Risk Factors For Gfr Decline In Childhmentioning
confidence: 95%